Pengembangan Media Pembelajaran Virtual Reality Berbasis Museum Klinik Santa Maria Kota Metro pada Materi Sejarah SMA - Bahtiar Afwan (UIN Imam Bonjol Padang, 2023)
The purpose of this research is to develop virtual reality learning media by integrating material from the history of the local clinic at the Santa Maria Museum at one of the high schools in Metro City. The method used in research uses research development (R&D) methods. The research stages include the analysis, design, development, implementation, and evaluation stages. The subjects in this study consisted of two material expert validators, two media expert validators, 40 high school class XI students, and one history teacher. The results of the development research show that virtual reality media based on the Santa Maria Clinical Museum has been proven valid and feasible based on the assessment of material experts and media experts. Based on the results of small group trials, limited group trials, and large trials, it was shown that virtual reality learning media based on the Santa Maria Clinical Museum proved to be effective and fit the needs of the analysis.